Big Cats 2017
DOI: 10.5772/intechopen.69558
|View full text |Cite
|
Sign up to set email alerts
|

Ecology and Evolution of Melanism in Big Cats: Case Study with Black Leopards and Jaguars

Abstract: Variations in animal coloration have intrigued evolutionary biologists for a long time. Among the observed pigmentation polymorphisms, melanism has been reported in multiple organisms (influencing several biological factors), and classical hypothesis has suggested that such variant can present adaptive advantages under certain ecological conditions. In leopards (Panthera pardus) and jaguars (Panthera onca), melanism is caused by recessive and dominant mutations in the ASIP and MC1R genes, respectively. This ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
27
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 52 publications
2
27
0
6
Order By: Relevance
“…Of the six felid species that occupy Costa Rica, three are known to exhibit melanistic polymorphisms-jaguar (Panthera onca), jaguarundi (Herpailurus yagouaroundi), and northern tiger cat (Leopardus tigrinus oncilla); there are no records of melanistic puma (Puma concolor) or ocelot (Leopardus pardalis) in Costa Rica, and melanistic margay (Leopardus wiedii) have only recently been reported . It is reported that about 10% of jaguars globally are melanistic (Silva, 2017), and melanism in this species is inherited as a dominant trait caused by a 15-bp deletion in the MC1R gene that produces eumelanin in the background regions of the coat (Eizirik et al, 2003;Haag et al, 2010). As of this writing, there are only two published records of melanistic jaguar in Costa Rica in this century (Cart ın & Carrillo, 2009;Sa´enz-Bolaños et al, 2015).…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…Of the six felid species that occupy Costa Rica, three are known to exhibit melanistic polymorphisms-jaguar (Panthera onca), jaguarundi (Herpailurus yagouaroundi), and northern tiger cat (Leopardus tigrinus oncilla); there are no records of melanistic puma (Puma concolor) or ocelot (Leopardus pardalis) in Costa Rica, and melanistic margay (Leopardus wiedii) have only recently been reported . It is reported that about 10% of jaguars globally are melanistic (Silva, 2017), and melanism in this species is inherited as a dominant trait caused by a 15-bp deletion in the MC1R gene that produces eumelanin in the background regions of the coat (Eizirik et al, 2003;Haag et al, 2010). As of this writing, there are only two published records of melanistic jaguar in Costa Rica in this century (Cart ın & Carrillo, 2009;Sa´enz-Bolaños et al, 2015).…”
mentioning
confidence: 98%
“…Of the 41 species of felids (Kitchener et al, 2017), 14 species exhibit a melanistic (black) coat morph that coexists with a wild-type "non-melanistic" coat pattern of visible spots, rosettes, or uniform color (Graipel et al, 2019;Schneider et al, 2012;Silva, 2017;Silva et al, 2016). The presence of alternative color morphs that coexist within a population, called coat color polymorphism, has long presented an evolutionary puzzle (Forsman et al, 2008;Graipel et al, 2014).…”
mentioning
confidence: 99%
See 3 more Smart Citations